Phase-frequency controlled In virtual synchronous converter for low-voltage microgrid-inverter synchronization - Amin, Md Ruhul; Zulkifli, Shamsul Aizam (Gazi University, 2017)
This paper explains an internal voltage controlled based on generator swing technique/dynamic response for inverter using virtual synchronous converter (VSCon) in order to achieve synchronization voltage between grid and inverter. As known, PLL is a common technique that is used to synchronize the amplitude, phase-angle and frequency between grid and source voltage. The VSCon is a technique which does not require any phase-locked-loop (PLL) circuit as an external control structure/source for the inverter to be synchronization with the grid. This VSCon has been modeled and simulated in inverter control using Matlab/Simulink software, which is connected to single-phase ac source input system connected and several loads. This VSCon has been implemented in inverter control strategy to generate reference voltage for pulse width modulation (PWM) signal that responds to the grid information in order to instruct the inverter voltage to be synchronized with the grid voltage. Several simulation tests have been conducted in order to prove the reliability of this VSCon. It is also has been tested if the grid frequency is changed from the rated frequency (50Hz) to 51Hz while at the meantime the phase-angle also has changed where the resulting results show that, VSCon takes nearly 40ms to synchronize to these changes.